The Influence of Ocean Current Patterns on Surface Marine Debris Distribution In Makassar City Waters - Faizal, Ahmad; Werorilangi, Shinta; Samad, Wasir (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2023)
A survey of the abundance and distribution of macro debris (>2.5 - <100 cm) and meso-debris (>0.5 – <2.5 cm) has been carried out in Makassar City waters. This research was carried out to map the distribution of surface marine debris following ocean current patterns. The macro debris abundance range is 2222-17222 items/km2 and the meso-debris range is 2222-30556 items/km2, with the dominance of 47,03% plastic debris for macro sizes and 49,74% wood debris for meso-sizes. The highest abundance was found at the Jeneberang estuary, then at the Losari Coastal Waters and the lowest at the mouth of the Tallo River. The current pattern in Makassar City waters at low or high tide tends to move from north to south towards the  Jeneberang River estuary, with the current speed getting southern and slower. This condition causes a high abundance of macro and meso debris at the mouth of the Jeneberang River.